Trichoderma and Bacillus multifunctional allies for plant growth and health in saline soils: recent advances and future challenges - Santoyo, Gustavo; Orozco-Mosqueda, Ma. del Carmen; Afridi, Muhammad Siddique; Mitra, Debasis; Valencia-Cantero, Eduardo; Macías-Rodríguez, Lourdes (Frontiers in Microbiology, 2024)
Saline soils pose significant challenges to global agricultural productivity, hindering crop growth and efficiency. Despite various mitigation strategies, the issue persists, underscoring the need for innovative and sustainable solutions. One promising approach involves leveraging microorganisms and their plant interactions to reclaim saline soils and bolster crop yields. This review highlights pioneering and recent advancements in utilizing multi-traits Trichoderma and Bacillus species as potent promoters of plant growth and health. It examines the multifaceted impacts of saline stress on plants and microbes, elucidating their physiological and molecular responses. Additionally, it delves into the role of ACC deaminase in mitigating plant ethylene levels by Trichoderma and Bacillus species. Although there are several studies on Trichoderma-Bacillus, much remains to be understood about their synergistic relationships and their potential as auxiliaries in the phytoremediation of saline soils, which is why this work addresses these challenges.